Overexpression of a Mycobacterium ulcerans Ag85B-EsxH Fusion Protein in Recombinant BCG Improves Experimental Buruli Ulcer Vaccine Efficacy. - Bryan E Hart; Sunhee Lee (Public Library of Science (PLoS), 2016)
Buruli ulcer (BU) vaccine design faces similar challenges to those observed during development of prophylactic tuberculosis treatments. Multiple BU vaccine candidates, based upon Mycobacterium bovis BCG, altered Mycobacterium ulcerans (MU) cells, recombinant MU DNA, or MU protein prime-boosts, have shown promise by conferring transient protection to mice against the pathology of MU challenge. Recently, we have shown that a recombinant BCG vaccine expressing MU-Ag85A (BCG MU-Ag85A) displayed the highest level of protection to date, by significantly extending the survival time of MU challenged mice compared to BCG vaccination alone. Here we describe the generation, immunogenicity testing, and evaluation of protection conferred by a recombinant BCG strain which overexpresses a fusion of two alternative MU antigens, Ag85B and the MU ortholog of tuberculosis TB10.4, EsxH. Vaccination with BCG MU-Ag85B-EsxH induces proliferation of Ag85 specific CD4+ T cells in greater numbers than BCG or BCG MU-Ag85A and produces IFNγ+ splenocytes responsive to whole MU and recombinant antigens. In addition, anti-Ag85A and Ag85B IgG humoral responses are significantly enhanced after administration of the fusion vaccine compared to BCG or BCG MU-Ag85A. Finally, mice challenged with MU following a single subcutaneous vaccination with BCG MU-Ag85B-EsxH display significantly less bacterial burden at 6 and 12 weeks post-infection, reduced histopathological tissue damage, and significantly longer survival times compared to vaccination with either BCG or BCG MU-Ag85A. These results further support the potential of BCG as a foundation for BU vaccine design, whereby discovery and recombinant expression of novel immunogenic antigens could lead to greater anti-MU efficacy using this highly safe and ubiquitous vaccine.